The Role of Bacterial Proteases in Microbe and Host-microbe Interactions - Hammers, Daniel; Carothers, Katelyn; Lee, Shaun (Current Drug Targets, 2022)
Background: Secreted proteases are an important class of factors used by bacterial to modulate their extracellular environment through the cleavage of peptides and proteins. These proteases can range from broad, general proteolytic activity to high degrees of substrate specificity. They are often involved in interactions between bacteria and other species, even across kingdoms, allowing bacteria to survive and compete within their niche. As a result, many bacterial proteases are of clinical importance. The immune system is a common target for these enzymes, and bacteria have evolved ways to use these proteases to alter immune responses for their benefit. In addition to the wide variety of human proteins that can be targeted by bacterial proteases, bacteria also use these secreted factors to disrupt competing microbes, ranging from outright antimicrobial activity to disrupting processes like biofilm formation. Objective: In this review, we address how bacterial proteases modulate host mechanisms of protection from infection and injury, including immune factors and cell barriers. We also discuss the contributions of bacterial proteases to microbe-microbe interactions, including antimicrobial and anti- biofilm dynamics. Conclusion: Bacterial secreted proteases represent an incredibly diverse group of factors that bacteria use to shape and thrive in their microenvironment. Due to the range of activities and targets of these proteases, some have been noted for having potential as therapeutics. The vast array of bacterial proteases and their targets remains an expanding field of research, and this field has many important implications for human health.
Keywords: therapeutics